The impact of nonperforming loans on cross-border bank lending implications for emerging market economies - Park, Cyn-Young; Shin, Kwanho (ADB Briefs, 2020)
This brief suggests how policy makers can tackle the likely rise in nonperforming loans (NPLs) as a result of the coronavirus disease (COVID-19) pandemic to prevent a debt crisis.